Representations of the East in the poetry of Bryon: A Study in Culture and Identity - Evans, H G (Department of English Language and Literature, 2023)
Edward Said's notion of 'orientalism' is explored with reference to a cross-section of Byron's narrative verse, taken chronologically. Particular focus is placed on two textual loci, namely, the concepts of 'culture' and 'identity'. These concepts form the basis of a close reading of both the texts themselves, and the manner in which Byron's personal and textual personas shape the narrative and are in turn influenced by their social context. An additional theme of exile is considered, and forms the bridge between a historical analysis of the verse, and current political reality as it is depicted in J.M. Coetzee's recent novel. Disgrace